Acupuncture and cellular mechanisms: the role of foxo transcription factors in autophagy and senescence - Zhou, Lizhi; Li, Xuying; Ao, Jinbi; Duan, Na (Journal of the Pakistan Medical Association, 2024)
The current narrative review was planned to elucidate the interplay between acupuncture, a cornerstone of Traditional Chinese Medicine, and the modulation of cellular mechanisms via Forkhead box O transcription factors, focussing on autophagy and cellular senescence. Autophagy, essential for cellular health, and cellular senescence, associated with aging and age-related diseases, are both significantly influenced by Forkhead box O transcription factors among other regulatory factors and pathways. These factors, known to diminish with age, play a pivotal role in promoting longevity. The current review analysed experimental models demonstrating acupuncture’s capacity to activate Forkhead box O transcription factors, thereby inducing autophagy and reducing cellular senescence. Evidence from studies on human fibroblasts, aging animal models, obesity-induced insulin resistance, and osteoporosis corroborates the beneficial effects of acupuncture. —Continue